Cyclo(-Phe-Phe) alleviates chick embryo liver injury via activating the Nrf2 pathway. Issue 13 (9th June 2022) - Zhang, Qiong-Yi; Han, Shao-Cong; Huang, Rong-Ping; Jiang, Man-Ya; Yan, Chang-Yu; Li, Xi-You; Zhan, Yu-Jiao; Li, Xiao-Min; Li, Yi-Fang; Kurihara, Hiroshi; Tan, Rui-Rong; Li, Wei-Xi; et al.
Abstract : Cyclo (Phe-Phe) ameliorated hepatic injury and dysplasia induced by oxidative stress, and the mechanism is mainly via promoting Nrf2 translocation as well as activating the Nrf2 pathway through binding Keap1. Abstract : Excessive reactive oxygen species (ROS) accumulation is involved in the pathogenesis of liver fibrosis and damage, specifically in the developing embryo that is extremely sensitive to oxidative stress. Herein, a liver injury model in chick embryo was established by using 2, 2-azobis (2-amidinopropane) dihydrochloride (AAPH), which was used to investigate the effect of cyclo(-Phe-Phe) (CPP), a natural dipeptide found in foods and beverages. The results showed that CPP significantly alleviated AAPH-induced liver pathological damage, hepatic dysfunction and inhibited the excessive production of ROS in both chick embryo liver and HepG2 cells. Additionally, CPP increased the antioxidative activity of glutathione peroxidase (GPx) and superoxide dismutase (SOD), as well as elevated the level of glutathione (GSH), suggesting that CPP combating liver injury probably depends on its antioxidant capability. Mechanistically, CPP upregulated the mRNA and protein expression of heme oxyense-1 (HO-1) and NADPH quinone oxidoreductase 1 (NQO1) in vivo and in vitro, along with promoting the translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) while inhibiting its degradation through binding with Kelch-like ECH-associated protein 1 (Keap1). In conclusion, this study proposes a potential peptide drug for the treatment of hepatic damage induced by oxidative stress and also unravels its mechanism of action.